Psychological Effects on the poetry of Sahir Ludhianvi - Bibi, Zakia; Khan, Sttar; Zaman, Shazia (sourcecoder, 2023)
Sahir Ludhianvi is a well-known poet of Urdu. He wrote odes, poems and songs. He was a very sensitive man. He always remained disappointed and frustrated. Sahir Ludhianvi was at a time romantic and progressive poet. He was the son of a very rich man, but his childhood passed in a very straitened circumstances. He was a frenzied lover and worshiped the women like a goddess. Many women came in his life as beloveds, but he could not succeed to make one of them as a partner of life. He remained bachelor. Some people say that he was impotent while the others think that the main reason was his carelessness and recklessness.Every poem of sahir is the result of his personal accident. He was at a time suffering from inferiority and superiority complex. The mother of Sahir was badly neglected by his father and she was divorced. Therefore psychological effects on his poetry are very prominent. His poetry is the voice of a thirsty lips lover.